Suppression of H2-cooling in protogalaxies aided by trapped Lyα cooling radiation. Issue 1 (9th October 2020) - Wolcott-Green, Jemma; Haiman, Zoltán; Bryan, Greg L
ABSTRACT: We study the thermal evolution of UV-irradiated atomic cooling haloes using high-resolution three-dimensional hydrodynamic simulations. We consider the effect of H − photodetachment by Ly α  cooling radiation trapped in the optically-thick cores of three such haloes, a process that has not been included in previous simulations. Because H − is a precursor of molecular hydrogen, its destruction can diminish the H2 abundance and cooling. We find that the critical UV flux for suppressing H2 -cooling is decreased by ∼15–50 per cent in our fiducial models. Previous one-zone modelling found a larger effect, with J crit reduced by a factor of a few; we show that adopting a constant halo mass to determine the trapped Ly α  energy density, as is done in the one-zone models, yields a larger reduction in J crit, consistent with their findings. Our results nevertheless suggest that Ly α  radiation may have an important effect on the thermal evolution of UV-irradiated haloes, and therefore on the potential for massive black hole formation.